케이블 TV 망에서 노드 선택을 위한 휴리스틱 연구 - 정균락(Kyun Rak Chong) (韓國컴퓨터情報學會論文誌, 2008)
The cable TV network has delivered downward broadcasting signals from distribution centers to subscribers. Since the traditional coaxial cable has been upgraded by the Hybrid Fiber Coaxial(HFC) cable, the upward channels has expanded broadband services such as Internet. This upward channel is vulnerable to ingress noises. When the noises from the children nodes accumulated in an amplifier exceeds a certain level, that node has to be cut off to prevent the noise propagation. The node selection problem(NSP) is defined to select nodes so that the noise in each node does not exceed the given threshold value and the sum of Profits of selected nodes can be maximized. The NSP has shown to be NP-hard. In this paper, we have proposed heuristics to find the near-optimal solution for NSP. The experimental results show that interval partitioning is better than greedy approach. Our heuristics can be used by the HFC network management system to provide privileged services to the premium subscribers on HFC networks. 케이블 TV망은 분배센터에서 가입자에게 방송 신호를 내려보내는데, 하이브리드 파이버 동축케이블(HFC)이 사용된 뒤로는 상향채널을 인터넷 같은 광대역 서비스로 확장해 활용하고 있다. 그런데 이 상향채널은 잡음에 취약한데 한 노드의 증폭기에 누적된 자식노드로부터의 잡음이 어떤 수준을 넘게 되면, 잡음이 더 이상 전파되는 것을 막기 위해 해당되는 노드를 분리하는 것이 필요하게 된다. 각 노드에 이익이 주어질 때 노드 선택 문제(NSP)는 각 노드에 누적된 잡음이 주어진 임계값을 넘지 않으면서 선택된 노드의 이익의 합이 최대가 되게 노드들을 선택하는 문제인데 NP-hard임이 증명되어 있다. 본 논문에서는 NSP의 근사해를 구하는 휴리스틱들을 제안하고 비교 분석하였는데, 구간 분할 휴리스틱이 greedy 휴리스틱보다 더 우수한 결과를 보였다. 이 휴리스틱들은 HFC 운영 시스템에 구현되어, 사용료를 더 많이 지불하는 우수 고객들에 해당하는 노드를 케이블 TV망에서 가능한 분리하지 않음으로써 더 좋은 질의 서비스를 제공하는 데 사용할 수 있다.